Harnessing AI for COVID-19 Mitigation in Indonesia - Khoirun, Nisa; Sony Kartika, Wibisono; Muhammad Jogo, Samodro; Agung, Pangestu; Rosyid Ridlo, Al Hakim; Hadi, Jayusman; Riska, Suryani; Yanuar Zulardiansyah, Arief; Sriyadi, Sriyadi (Seventh Sense Research Group, 2025)
The Corona Virus Disease (COVID-19) pandemic has significantly challenged healthcare systems around the world, especially in developing countries such as Indonesia. This research explores the application of Artificial Intelligence (AI) in addressing various aspects of the pandemic, including diagnosis, prediction, telemedicine, and public health management. A systematic review of literature and case studies was conducted to analyze AI-driven approaches implemented in Indonesia. The findings reveal that AI technologies such as intelligent diagnostic systems, machine learning models, and mobile-based health solutions have contributed to mitigating the spread and impact of COVID-19. Despite the progress, challenges remain, including data privacy concerns and limited access to AI-driven healthcare tools. The study highlights the need for further integration of AI in healthcare policies and proposes recommendations for enhancing AI-driven public health interventions. Future research should focus on improving AI accessibility and ethical considerations in developing nations.